Investigating rural entrepreneur’s business performance in Malaysia - Mohd Zin, Md. Lazim; Hassan, Zuraida; Subramaniam, Chandrakantan (2015)
The present study attempts to provide empirical evidence on the relationship between the three facets of entrepreneurial initiatives and rural entrepreneurs business performance.The entrepreneurial initiatives considered in the study are business support, networking support, and financial support.Toward this end, a survey among 183 rural entrepreneurs was carried out. Self-reported measures were used to obtain data pertaining to government entrepreneurial initiatives and rural entrepreneurs’ business performance.The multiple regression analysis was used to ascertain the proposed relationships and it was found that only networking support had statistically significant relationship with rural business performance.However, business support and financial support were not related with business performance. Discussion on the findings is highlighted, so as the implications for practice and future research. Limitations of the study are also discussed.